IMPLEMENTASI PERATURAN BUPATI NOMOR 39 TAHUN 2011 TENTANG PELIMPAHAN BUPATI KEPADA CAMAT DI LINGKUNGAN PEMERINTAH KABUPATEN ROKAN HULU (Studi Kasus Problematika Pelimpahan Wewenang Bidang Perizinan oleh Camat Rambah Kabupaten Rokan Hulu Tahun 2013-2015) - Ridwan "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to know the implementation of tasks and authorities by the camat rambah in field permissions kecamtan rambah rokan hulu. as for the backdrop in this study the number there are obstacles in the exercise of duties and authorities head in taking care of business license in kecamatn rambah.This study uses qualitative methods with techniques of data collection by means of in-depth interviews and the utilization of the library as well as a descriptive qualitative data analysis. data required primary data among others obtained through interviews and secondary data obtained through study in the library-related research issues.Based on the results of the implementation of tasks and authorities head in the exercise of delegated authority by pelimpahan Regent Regent through number 39 in 2011 about the Pelimpahan authority to the head of environmental governance in the Rokan Hulu obscurity of technical instructions and executing instructions over the Regent rules led to an overlap of authority between the districts and other agencies.Keywords: implementation, the authority, the authority Pelimpahan